Service-level barriers to and facilitators of accessibility to treatment for problematic alcohol use: a scoping review - Dianna M. Wolfe; Brian Hutton; Brian Hutton; Kim Corace; Kim Corace; Kim Corace; Kim Corace; Nathorn Chaiyakunapruk; Nathorn Chaiyakunapruk; Surachat Ngorsuraches; Surapon Nochaiwong; Justin Presseau; et al. (Frontiers Media S.A., 2023)
IntroductionServices to treat problematic alcohol use (PAU) should be highly accessible to optimize treatment engagement. We conducted a scoping review to map characteristics of services for the treatment of PAU that have been reported in the literature to be barriers to or facilitators of access to treatment from the perspective of individuals with PAU.MethodsA protocol was developed a priori, registered, and published. We searched MEDLINE®, Embase, the Cochrane Library, and additional grey literature sources from 2010 to April 2022 to identify primary qualitative research and surveys of adults with current or past PAU requiring treatment that were designed to identify modifiable characteristics of PAU treatment services (including psychosocial and pharmacologic interventions) that were perceived to be barriers to or facilitators of access to treatment. Studies of concurrent PAU and other substance use disorders were excluded. Study selection was performed by multiple review team members. Emergent barriers were coded and mapped to the accessibility dimensions of the Levesque framework of healthcare access, then descriptively summarized.ResultsOne-hundred-and-nine included studies reported an extensive array of unique service-level barriers that could act alone or together to prevent treatment accessibility. These included but were not limited to lack of an obvious entry point, complexity of the care pathway, high financial cost, unacceptably long wait times, lack of geographically accessible treatment, inconvenient appointment hours, poor cultural/demographic sensitivity, lack of anonymity/privacy, lack of services to treat concurrent PAU and mental health problems.DiscussionBarriers generally aligned with recent reviews of the substance use disorder literature. Ranking of barriers may be explored in a future discrete choice experiment of PAU service users. The rich qualitative findings of this review may support the design of new or modification of existing services for people with PAU to improve accessibility.Systematic Review RegistrationOpen Science Framework doi: 10.17605/OSF.IO/S849R.